Personalisation in social work - Gardner, Ali (London : Learning Matters, an imprint of SAGE Publications Ltd., 2014)
The government agenda on Personalisation and self-directed support is fast-moving and rapidly changing. It is vital therefore that students and practitioners alike are aware of the key issues and debates, as well as the policy that surrounds this area of practice. This timely and fully revised second edition provides an overview of the personalisation agenda and looks at the recent legislation in a broad historical and theoretical perspective. This approach will provide opportunities for students to consider the changes to the social work role and to evaluate the impact of this for service users and as practitioners.
Previous edition: 2011.
Includes bibliographical references and index.
Keywords: Community-based social services -- United Kingdom; Patient participation -- United Kingdom